The Evaluation of a Tactile Display for Dismounted Soldiers in a Virtusphere Environment. (September 2013) - Chapman, Roger J.; Nemec, MAJ Lou; Ness, COL James
Here we describe the evaluation of the THATO (TeleHaptic Assistance for Tactical Operations) mobile tactile messaging system in a "virtusphere" environment. THATO was developed to aid dismounted soldier-to-soldier communications, situation awareness, and navigation during tactical operations. The THATO Android application stores tactile message designs that are instantiated with context specifics and played through its interface to Tactile Control Units (TCUs) when a command is received from another soldier, the soldier's location relative to a planned route or landmark/entity of interest triggers a message, or the soldier requests information (e.g. through voice recognition). Two previous evaluations of THATO and its evolving language produced promising results, but only six participants were involved in each and the fidelity was limited with participants simply standing and verbalizing their interpretations of messages played in a random order. Here the results of a lab experiment are presented where twenty participants were involved and fidelity was improved by having participants also respond to messages with appropriate physical behaviors within a 10 foot hollow sphere capable of rotating upon wheels placed beneath it. Overall, participants received twelve types of message, each with between one and four pieces of information, and recognized all parts of a message 95.9% of the time.